PERSENTASE BOBOT BAGIAN SALURAN PENCERNAAN TERNAK AYAM KAMPUNG UNGGUL BALITNAK (KUB) SISTEM FREE RANGE PADA PADANG PENGGEMBALAAN INTRODUKSI CLITORIA TERNATEA - Helda, Helda; Koten, Bernadetta B.; Kolloh, Ruben (Partner, 2024)
ABSTRACTThe objective of this research was to evaluate the percentage of the digestive tract components in KUB chickens reared in a Free-Range system on Clitoria ternatea pastures. This study was conducted at Afro Farm from September to November 2022. The research materials consisted of 70 eight-week-old female KUB chickens with body weights ranging from 300 to 400 grams each. The self-mixed feed had nutritional content with a Metabolic Energy of 2,949.04 Kcal/kg, crude protein of 17.11%, crude fat of 4.94%, crude fiber of 4.95%, calcium of 1.07%, phosphorus of 0.92%, methionine of 0.47%, lysine of 0.91%, and Clitoria ternatea pasture. The experimental design used was a Completely Randomized Design (CRD) with 2 treatments and 7 replications, where R0 represented intensive KUB chicken husbandry and R1 represented Free-Range KUB chicken husbandry, followed by a t-test. The results of the research showed that Free-Range husbandry significantly affected (P<0.05) the percentage of digestive tract components compared to intensive husbandry. The t-test results, except for the percentage of Gizzard weight (1.69<2.17), showed differences between the Free-Range and intensive systems, with the percentage of Proventriculus weight (5.51>2.17), Small Intestine (5.50>2.17), and Cecum (4.13>2.17) being higher in the Free-Range system. The results indicate that the Free-Range husbandry system on Clitoria ternatea pastures can be an alternative for KUB chicken rearing because it has a positive impact on the percentage of KUB chicken digestive tract component weights, except for the gizzard, which showed no difference. Based on this research, it can be concluded that the Free-Range system on Clitoria ternatea pastures can be considered as an alternative husbandry method for KUB chickens due to its positive effect on the percentage of KUB chicken digestive tract component weights.Keywords: Percentage of digestive tract component weight, KUB chicken, Free-Range, Clitoria ternatea.